Zues Vanilla Cafe / Muhammad Eidlan Hakimi Radzi ... [et al.] - Radzi, Muhammad Eidlan Hakimi; Mohamad Zahari, Muhammad Zaid; Azahar, Nurul Anis Syamimi; Ramizi, Noor Umaira Aziera (2021)
ZUES Vanilla Cafe was founded by four members which is Zaid, Eidlan, Umaira and Syamimi. This business has created because of the use of natural vanilla extract is seen to be quite rare in Malaysia due to the lack of exposure to vanilla extract. Therefore, we took this opportunity to build a Cafe concept business that offers food products based on natural vanilla extract such as cupcakes, ice blended, ice cream and vanilla buns where vanilla pulp suppliers can be obtained from vanilla tree planting operators. This is because even though the price is quite expensive when compared to the artificial vanilla flavor, the natural vanilla extract will affect the taste and feel of the food, drinks and desserts that will be produced. In running our marketing strategy, we started selling by promoting and started taking orders via Facebook, website and Instagram. In addition, we also did a banner to promote our products to our target customers such as teenagers and young people that can notice our café create some varieties food products using vanilla extract. Our products have many benefits by using natural vanilla extract where this vanilla is an aroma enhancer in food and beverages, an appetite enhancer, avoids the risk of cancer and good for reducing stress. Every member in this company has their own professional skills. Eidlan as our General Manager and Operation Manager really knows how to plan or control the overall management of the business. He also really professional in managing the production if goods activities. Thus, Syamimi really professional in her line of work which is maintaining administrative department by selecting, orienting and training employees. Zaid also really committed and professional in his scope of work which is managing product advertising for promoting to public. Lastly, Umaira knows how to drafting the plan to develop the business for long terms financial goals in the company. On the financial side, Umaira in charge of deciding cash inflow and outflow. We need a capital of RM200,000 to start a business and will use it to buy raw materials, offices equipment, machineries, marketing uses and so on. For the first year, we aim that our sales reach RM578,000 and the cash surplus for every year around RM70,000 to RM130,000. With the surplus money, we roll it back as operation cost and all other expenses as well as it shows good achievement for our business.